Market dynamics associated with credit ratings - a literature review - Fernando Gonzalez; François Haas; Ronald Johannes; Mattias Persson; Liliana Toledo; Roberto Violi; Martin Wieland; Carmen Zins (European Central Bank (ECB), 2004)
This paper investigates the potential impact of the growing influence of the opinions of credit rating agencies (CRAs) on market dynamics. This impact can be seen as a consequence of the information content of the ratings themselves or indirectly as a consequence of the "hardwiring" of ratings into regulatory rules, management mandates, bond covenants, etc. Rating agencies who strive to provide credit assessments that remain broadly stable through the course of the business cycle have been themselves affected as the growing reliance on rating mean that they are increasingly expected to satisfy a widening range of constituencies with different and sometimes conflicting interests. They have responded to this challenge largely by adding more products to their traditional product palette but also through modifications in the rating process. It is however too early to say whether these changes mean a fundamental shift in their approach to credit risk measurement.
Keywords: G10; G28; G29; 330; credit rating agencies; ratings; market dynamics; rating triggers; rating methodologies.; Kreditwürdigkeit; Kreditrisiko; Informationswert; Kreditmarkt